2016
DOI: 10.1161/circinterventions.116.004092
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Ectasia Are Frequently Observed in Patients With Bicuspid Aortic Valves With and Without Dilatation of the Ascending Aorta

Abstract: Background— The presence of coronary artery ectasia (CAE) is influenced by genetic factors and related to the presence of aneurysms in other vascular beds. Bicuspid aortic valve (BAV) disease is frequently accompanied by ascending aortic aneurysm. Because the aortic valve and the proximal parts of the coronary arteries share a common embryonic origin, we hypothesized that CAE is associated with BAV disease. Methods and Results— One hundred seventy-seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The coexistence with other conditions, such as BAV and aortic aneurysms, corroborates the conception of CAE as the manifestation of a systemic disease, in which individual genetical susceptibility might be one of the contributing factors (17,28).…”
Section: Etiopathogenesis and Pathophysiologysupporting
confidence: 71%
See 1 more Smart Citation
“…The coexistence with other conditions, such as BAV and aortic aneurysms, corroborates the conception of CAE as the manifestation of a systemic disease, in which individual genetical susceptibility might be one of the contributing factors (17,28).…”
Section: Etiopathogenesis and Pathophysiologysupporting
confidence: 71%
“…CAE has been frequently reported in patients with aneurysms in other vascular beds, such as ascending and abdominal aorta and pulmonary arteries (27). Moreover, Meindl et al found that CAE was a common finding in patients with bicuspid aortic valve (BAV), with or without aneurysms of the ascending aorta (28).…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, CAE was also frequently observed in patients with ascending aorta aneurysms or bicuspid aortic valves. [11, 12] The major histological features of AAA include chronic medial and adventitial inflammation with medial degeneration, including smooth muscle cell apoptosis and excessive loss of extracellular matrix (ECM), especially extensive elastin fragmentation. [13, 14] Similarly, ectatic coronary arterial walls also demonstrate marked degradation of the medial collagen and elastin fibres, with disruption of the internal and external elastic lamina.…”
Section: Discussionmentioning
confidence: 99%
“…This approach included the case when the entire artery was conspicuously large without a normal segment. [11] The severity of CAE was determined according to the Markis classification. [8] Diffuse ectasia of 2 or 3 vessels was classified as type I, diffuse disease in 1 vessel and localized disease in another vessel as type II, diffuse ectasia of only 1 vessel as type III, and localized segmental ectasia as type IV.…”
Section: Methodsmentioning
confidence: 99%
“…Association of BAV with anomalous coronary arteries has been reported 3 , 4 . Several studies have uncovered significantly increased prevalence of CAAs, such as the absence of the left coronary artery (LCA) in BAV patients compared with their tricuspid counterparts, and BAV patients with coronary anomalies have more postoperative ischemic cardiac events and increased morbidity 5 9 . Furthermore, recent genome-wide analysis has identified variant loci in patients with aortic valve stenosis associating with BAV and coronary artery disease, suggesting shared genetic predisposition 10 .…”
Section: Introductionmentioning
confidence: 99%